Early Adolescent Impulsivity in New Trends and Impact on Psychosocial Development - Almuthii'ah, Khadijah; Luthfiyah, Luthfiyah; Nadiya Dewi Syahida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Impulsivity is a personality trait characterized by a lack of careful thought. This trait tends to be dangerous if there are no boundaries, especially in early adolescents who do not yet have a mature prefrontal cortex to think about their actions. This study used a literature review method with data search using the latest scientific journals or articles from PubMed, Google Scholar, and ResearchGate. This review found that impulsivity stems from neurophysiological, neural biological, limbic system, and psychological factors that impact adolescents. Adolescents affected by interpersonal issues may be more likely to engage in risky behaviors and experience increased psychological pressure. Consequently, impulsivity in adolescents has the potential to become an issue if not addressed through preventive measures, such as implementing positive reinforcement, practicing mindfulness, controlling self-control, and Impulsive Decision Reduction Training for Youth (IDRT-Y). It is advisable to prevent impulsivity in early adolescence to promote more mature thinking.